Collaborative practical theology : engaging practitioners in research on Christian practices - Roest, Henk de, 1959- (Theology in Practice;, 2020)
"Collaborative Practical Theology documents and analyses research on Christian practices conducted by academic practical theologians in collaboration with practitioners of different kinds in Christian practices all around the world. These practitioners include professional practitioners, everyday believers, volunteers and students in theological education. The book offers rationales for setting up joint investigation groups with different 'communities of practice', describes a wide range of collaborative research strategies and methods and also has a clear eye for their limitations. In Christian practices faith is mediated, enacted and nurtured. The aim of the book is to improve the utility of theological research on these practices. It communicates the vision that academic research is for the people of God in today's world".